Translating PSM Policy into Production Practices - Te Walvaart, Marleen (VIEW Journal of European Television History and Culture, 2019)
PSM policy documents aim at interactive audience engagement, but production practices show many limitations to achieve this. This article studies how PSM policy is translated into practice, by analysing the newsroom management strategies about audience engagement. In-depth interviews were conducted with managers at different levels of the Flemish public service company VRT. Results show that managers primarily aim at immersive engagement through newsroom convergence and VRT brands. They value interactive engagement as well, but those experiments remain vulnerable. Newsroom management strategies are closely based on practices and audience behaviour, while there is a much larger distance with broader VRT policy.